Interventions in Nutrition Education for Improving the Performance of Integrated Health Care - Alam, Syamsul; Bahar, Burhanuddin (Al-Sihah: The Public Health Science Journal, 2021)
The description of community behavior in utilizing existing health service facilities in their area can be seen from the success rate of the Posyandu program, namely the coverage of weighing children under five at the Posyandu. This study aims to examine that nutrition education interventions through community nutrition classes can increase the scope of integrated health care (posyandu) performance (D/S, N/D) in Bulukumba Regency, Indonesia. This research design is quasi-experimental. The samples in this study were mothers of children under five who were in the intervention area (n=107) and control (n=113). The intervention group was given nutrition education through community nutrition class activities, while the control group was given counseling. The results showed that there were changes in the intervention group in the form of increased knowledge of mothers of children under five, increased parenting patterns of mothers of children under five, increased levels of community participation, and increased body weight of toddlers compared to the intervention group. control group. Community nutrition classes at posyandu can be used as a model in increasing the level of community participation in posyandu because there are changes in both knowledges, child care patterns, the number of visits at posyandu (D/S), and the number of toddlers who experience weight gain from the previous month’s weighing (N/D) for increased significantly.